Determinants of Motor Vehicle Tax Compliance among Generation Z in the Digital Era: The Mediating Role of Tax Sanctions - Reza Maharani; Retno Handayani (MASI Mandiri Edukasi, 2026)
Motor vehicle tax compliance remains a critical issue in supporting Regional Original Revenue (PAD), particularly among Generation Z, who are increasingly dominant in the productive population but often exhibit low compliance behavior. This study aims to analyze the factors influencing motor vehicle tax compliance among Generation Z in Kediri Regency, focusing on digital tax services, e-wallet effectiveness, social media exposure, income level, and tax sanctions. This research employs a quantitative approach using primary data collected through questionnaires distributed to 62 respondents aged 17–26 years who are responsible for paying motor vehicle taxes. Data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS 4 to evaluate both direct and indirect relationships among variables. The results show that tax sanctions have a positive and significant effect on motor vehicle tax compliance, indicating that enforcement plays a dominant role in shaping compliance behavior. E-wallet effectiveness also demonstrates a significant influence, suggesting its role in supporting compliance through indirect mechanisms. In contrast, digital tax services, social media exposure, and income level do not have a significant direct effect on compliance. These findings indicate that technological accessibility alone is insufficient to improve compliance without consistent enforcement of sanctions.